Proposed Business Strategy to Increase Competitiveness of Genta Guitar - Farras, Muhammad Ramzy (Fakultas Ekonomi, Universitas Muslim Indonesia, 2024)
This study aims to develop a business strategy for Genta Guitar to enhance its competitiveness in Indonesia’s rapidly growing guitar market. Employing internal and external analysis tools, including Value Chain Analysis, VRIO, PESTEL, and Porter’s Five Forces, the research identifies strategic gaps affecting Genta Guitar’s sales performance. By synthesizing findings into a SWOT analysis and refining strategies using the TOWS Matrix, this paper proposes actionable recommendations. The results highlight the need for improved brand recognition, optimized distribution channels, and tailored marketing strategies. Implementation of these strategies can close existing gaps, enhance competitiveness, and drive sustainable growth in the local market.